Field reports form for submitting seasonal observations of Iowa birds, Jan L. Walter, fall 1997 - Walter, Jan L.et al (1997)
Fall report of birds found in Mason City contributed by Jan L. Walter. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1997. Epson - sheet feed